Efektivitas model kooperatif tipe Team Assisted Individualization (TAI) terhadap pembelajaran matematika - Pratiwi, Anting (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the effectiveness of the application of mathematics learning through the Team Assisted Individualization (TAI) type of cooperative learning model. This type of research is an experiment involving one class as an experimental class without a control class, and the research design used is One Group Pretest Posttest Design. The sample in this study was grade IV students for the 2021/2022 academic year as many as 20 people. This study refers to two of the four aspects of learning effectiveness criteria, namely; student learning outcomes and activities. A learning can be said to be effective if two of these aspects are met with the condition that aspects of learning outcomes are learning mastery taken from the difference between learning outcomes before and after treatment. The instrument used is a test of learning outcomes to observe student activities. The results showed that: (1) the average score of students' mathematics learning outcomes after the TAI type cooperative learning model was applied was 78.00 and was in the medium category with a standard deviation of 5.71 where the highest score was 90.00 and the lowest score was 70.00. from the ideal score of 100. From these results, 16 students or 80% achieved individual mastery, 4 students or 20% did not achieve individual mastery and that means classical mastery was achieved. (2) the average percentage of student activity frequency, which is 88 of the indicators for student activity criteria, has reached the active criteria. From the results of this study, it can be concluded that the Team Assisted Individualization (TAI) type of cooperative learning model is effectively applied in learning mathematics for fourth grade students.